Cocoa : a trader's guide - International Trade Centre UNCTAD/GATT; Curtis, Bronwyn N. (Geneva : International Trade Centre, 1987)
A handbook on cocoa export marketing and trade practices, including producing countries' internal marketing systems; cocoa export mechanisms; commodity market operations, futures trading procedures; information sources and techniques; cocoa export financing arrangements; and processing enterprises' purchasing strategies.
Includes bibliographical references p. 253-269
eej 14/01/2019
Loans
Keywords: Cocoa trade; Commodity exchanges